LES investigation of heat transfer in a tube with irregular roughness at moderate Prandtl numbers - Garg, Himani ; 0000-0002-5223-0567; Kadivar, Mohammadreza (International Communications in Heat and Mass Transfer, 2025)
Wall-bounded turbulent flows are central to a wide range of engineering applications, where surface roughness can significantly influence both frictional drag and convective heat transfer. While the momentum effects of roughness have been significantly advanced in the literature, the thermal counter parts remain insufficiently understood. This study addresses the critical gap in understanding rough-wall turbulent heat transfer at higher Prandtl numbers. Using wall-resolved Large Eddy Simulations (LES), we investigate convective heat transfer in a tube with irregular Gaussian roughness across bulk Reynolds numbers ranging from 4000 to 15,000 and Prandtl numbers of 1, 3, 5, and 7. This study provides the first systematic examination of rough-wall turbulent heat transfer for Prandtl numbers greater than 2. Results showed a consistent increase in temperature roughness function () with Prandtl number (), while its variation with roughness Reynolds number () exhibited distinct trends between transitionally and fully rough regimes. The heat field reached the fully rough regime earlier than the momentum field, showing stronger sensitivity to , particularly for high- fluids. Heat transfer enhancement increased up to 4.5 times with increasing Reynolds number; however, frictional losses outweighed thermal gains, deviating from the Reynolds analogy. Increasing improved thermal gains without affecting friction, resulting in Reynolds analogy efficiency exceeding unity for ≥ 3. Based on these findings, a new correlation for Reynolds analogy efficiency is proposed, by introducing a Prandtl-number-dependent term.
Keywords: Heat transfer; Roughness; Turbulent boundary layers; Reynolds analogy; Turbulent flows; Numerical simulations; CFD modeling